ANALISIS PENDAPATAN PETANI PENYADAP GETAH PINUS (Pinus merkusii) METODE KOAKAN PADA HKM NUSANTARA HIJAU - Jaya, Waldi; Gautama, I.; Dassir, Muhammad (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
Household income in rural areas generally does not come from one source, but comes from two or more sources. One of the non-timber forest product (NTFP) commodities that provides a lot of potential and function to increase income is tapping pine resin. This research aims to calculate the income of pine sap tapping farmers and income from other sectors. This research was conducted in September 2023 at the HKm Nusantara Hijau work area, Laiya Village, Cenrana District, Maros Regency, South Sulawesi Province. Determining the population and sample for this study used the purposive sampling method by taking 20 people as respondents. Respondents were selected with the consideration that they had been tapping for more than one year, people who lived around the forest area and were members of the Nusantara Hijau forest farmer group, and made their main job as pine sap tapper. The total income obtained from tapping pine sap was IDR. 453,480,000/year. Pine sap tapping activities have provided an increase in the welfare of people who work as tapping farmers as evidenced by the difference in income from pine sap tapping activities and income from other sectors, where the average income from pine sap tapping is IDR. 22,674,000/year, higher than the average income from other sectors, namely Rp. 2,510,500/year.